2018
DOI: 10.1002/ptr.6226
|View full text |Cite
|
Sign up to set email alerts
|

The effects of curcumin‐containing supplements on biomarkers of inflammation and oxidative stress: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Besides other benefits, curcumin is getting more recognized for its antioxidant and anti-inflammatory properties, highlighting the importance of curcumin application for chronic disease prevention. This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to assess the influence of curcumincontaining supplements on biomarkers of inflammation and oxidative stress. MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of ControlledTrials were searched till January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 36 publications
7
69
1
2
Order By: Relevance
“…Thus, while research using curcumin supplements with improved bioavailability (Meriva Curcumin [4,5]; Theracurcumin Theravalues [1,24,25,36]; Longvida [30]; CurcuWIN [10]; CurcuFresh [32] determined the dose at values between 150 and 1500 mg/day, studies using curcumin naturally [28,31] needed higher doses (5000 to 6000 mg/day) to achieve similar bioavailability.…”
Section: Curcumin Supplementationmentioning
confidence: 99%
“…Thus, while research using curcumin supplements with improved bioavailability (Meriva Curcumin [4,5]; Theracurcumin Theravalues [1,24,25,36]; Longvida [30]; CurcuWIN [10]; CurcuFresh [32] determined the dose at values between 150 and 1500 mg/day, studies using curcumin naturally [28,31] needed higher doses (5000 to 6000 mg/day) to achieve similar bioavailability.…”
Section: Curcumin Supplementationmentioning
confidence: 99%
“…Meta-analyses of randomised controlled trials, which assessed the effect of curcumin-containing supplements on oxidative stress and inflammation biomarkers, have suggested that curcumin-containing supplements exert antioxidant and anti-inflammatory effects through significant reductions in circulating serum concentrations of a panel of mediators such as malondialdehyde, interleukin 6 (IL-6) and TNF-α (207)(208)(209)(210). While interleukin-6 is a multi-functional cytokine that plays a key role in carcinogenesis of many human cancers, TNF-α is one of the major molecular mediators of a wide range of chronic inflammation and inflammation-related disorders (211).…”
Section: Curcumin and Piperinementioning
confidence: 99%
“…72 The antiinflammatory effects probably occurred through interference at different levels of the arachidonic acid inflammatory cascade and inhibition of proinflammatory compounds such as prostaglandins, leukotrienes, and COX-2. 68,69 Of note, a C. longa rhizome extract even protected collagen-induced arthritic Sprague-Dawley rats from the degenerative changes in the bone and ankle joints to a comparable extent as betamethasone. 74 Importantly, clinical trials with curcumin produced encouraging results in patients with rheumatoid arthritis 75 and postoperative inflammation.…”
Section: Curcuma Longa Lmentioning
confidence: 99%
“…Microbial infections, HIV infection, rheumatic disorders, gastrointestinal ailments, headache and body aches 7, 39,40,41 Phenylpropanoids such as 1'S'-1'acetoxychavicol acetate, terpenes/ terpenoids such as β-pinene, flavonoids such as galangin and alpinin 43,44 Antimicrobial, [46][47][48][49][50] Diarylheptanoids including curcuminoids such as curcumin, diarylpentanoids, sesquiterpenes, monoterpenes, diterpenes, and triterpenoids [65][66][67] Antinflammatory, [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] chemopreventive and anticancer, [85][86][87][88][89][90][91][92] antimicrobial, 62,93-95 Antiparasitic, 96 anti-Alzheimer activity [97][98][99] Hedychium coronarium J.…”
Section: Aframomum Melegueta K Schummentioning
confidence: 99%
See 1 more Smart Citation